PENERAPAN STRATEGI PEMBELAJARAN LIGHTENING THE LEARNING CLIMATE UNTUK MENINGKATKAN MOTIVASI BELAJAR PENDIDIKAN KEWARGANEGARAAN (PKN) SISWA KELAS V SDN 06 LUBUK DALAM KABUPATEN SIAK - Untung Untung (JURNAL PAJAR (Pendidikan dan Pengajaran), 2017)
This research is motivated by the lack of motivation to learn citizenship education (Civics) student class V SDN06 Lubuk Dalam Kabupaten Siak. This study aims to find out the increase learning motivation citizenshipeducation (Civics) student class V SDN 06 Lubuk Dalam Kabupaten Siak through the lightening learningstrategies learning climate, held for 1 month. The subjects were class V SDN 06 Lubuk Dalam Kabupaten Siakthe number of students as many as 25 people. Form of research is classroom action research. The researchinstrument consists of instruments and instrument performance data collection activity observation sheet formteacher and student activity. Based on the research, the conclusion to this study is the use of learning strategieslightening the learning climate can improve students' motivation to learn civics class V SDN 06 Lubuk DalamKabupaten Siak. The above statement is supported by the results of the application of learning strategieslightening the learning climate motivation to learn civics. Where the first meeting of the first cycle is stillconsidered low by a total score of 104. The second meeting of the first cycle increased by a total score of 119, atthe first meeting of the second cycle also increases with total score of 149, student motivation was reached on atotal score of 166 or higher category. Motivation to learn civics class V students of SDN 06 Lubuk DalamKabupaten Siak reached on a total score of 166 or higher categories, and when viewed from the percentage ofstudents who demonstrate high motivation to learn there was 78.8%. So the research is successful, because theperformance indicators are being achieved.